Stakeholder involvement in the innovation process: An example in medical robotics, the ROBO-K project - Nathalie Pichot; Kévin Nadarajah; Isabelle Bonan; Guy Caverot; Pauline Coignard; Jean-Luc Le Guiet; Alain Somat (Annals of Robotics and Automation - Peertechz Publications, 2021)
In the field of medical robotics, many studies have called for the integration of end-users in the innovation process. The objective is to identify the factors that facilitate (or not) the use of the designed robots and thus try to guarantee their diffusion in the care services. This recommendation was followed in the ROBO-K project. The ROBO-K project proposes the design and development of a mobile, interactive robot dedicated to gait rehabilitation. This project was initiated by BA Healthcare, a medical robotics company. The design of a robot was accompanied to achieve the targeted therapeutic objectives by taking into account the requirements related to the needs of the patients and the practitioners; the care activity and the institutions involved. A follow-up by the social acceptability of the technology led to focus the innovation process on a co-construction activity involving all stakeholders. This co-construction activity was decisive, as it guided the definition of functional expectations and the technical specifications of the prototype developed. It was completed by a test phase of the prototype (in a care situation for 5 months). The results show the relevance to involve all the stakeholders in all the design and development phases of the robotic device. However, they underline the difficulties or limits linked to this type of approach in terms of innovation.